Abnormal temporal dynamics of visual attention in spatial neglect patients. - Husain, M; Shapiro, K; Martin, J; Kennard, C (1997)
When we identify a visual object such as a word or letter, our ability to detect a second object is impaired if it appears within 400ms of the first. This phenomenon has been termed the attentional blink or dwell time and is a measure of our ability to allocate attention over time (temporal attention). Patients with unilateral visual neglect are unaware of people or objects contralateral to their lesion. They are considered to have a disorder of attending to a particular location in space (spatial attention). Here we examined the non-spatial temporal dynamics of attention in patients, using a protocol for assessing the attentional blink. Neglect patients with right parietal, frontal or basal ganglia strokes had an abnormally severe and protracted attentional blink When they identified a letter, their awareness of a subsequent letter was significantly diminished for a length of time that was three times as long as for individuals without neglect. Our results demonstrate for the first time that visual neglect is a disorder of directing attention in time, as well as space.